RETRACTED: Do natural environmental protection, regional innovation climate, entrepreneurs’ cognition of green development positively influence the sustainable development of small rural businesses - Xingpeng Zheng; Jacquline Tham; Ali Khatibi (PLoS ONE, 2025)
In the era of the green economy, the Chinese government has advocated for natural environmental protection and innovation in rural areas, making the sustainable development of small rural businesses into a focal point. Currently, whether natural environmental protection promotes the sustainable development of small rural businesses remains debatable, and the roles of regional innovation climate, entrepreneurs’ cognition of green development, and technological innovation in production on the sustainable development of small rural businesses are often overlooked. Addressing this gap, this study draws inspiration from Upper Echelons Theory and Sustainable Development Theory to construct a structural equation model (SEM) and proposes 10 hypotheses. Primary data was collected from rural entrepreneurs across 17 provinces in China, yielding 439 valid samples. The data were analyzed using AMOS 28.0, SMARTPLS 4.0, and SPSS 28.0. The findings revealed that natural environmental protection did not positively influence the sustainable development of small rural businesses (β = 0.104, p > 0.05). In contrast, the regional innovation climate (β = 0.189, p = 0.001) and rural small business entrepreneurs’ cognition of green development (β = 0.261, p < 0.001) significantly affected the sustainable development of small rural businesses. Technological innovation in production (β = 0.034, p < 0.01) played a partial mediating role between the regional innovation climate and the sustainable development of small rural businesses. And, the mediating role of technological innovation in production was significant in the relationship between entrepreneurs’ cognition of green development and the sustainable development of small rural businesses (β = 0.059, p < 0.01). As a representative developing country, China’s findings in rural areas provide valuable insights for other developing countries undergoing green development transitions. This study not only questions the applicability of Porter’s hypothesis in rural contexts but also offers implications for relevant policymakers and small business entrepreneurs.